Antibiotic resistance profile and RAPD analysis of Campylobacter jejuni isolated from vegetables farms and retail markets - John Yew Huat, Tang; Che Abdullah, Abu Bakar; Mohd Ikhsan, Khalid (Hainan Medical University, 2016)
Objective: To investigate antibiotic resistance profile and characterize Campylobacter jejuni (C. jejuni) isolates using random amplified polymorphic DNA (RAPD) analysis.